Anxiety among older psychiatric patients: a hidden comorbidity?. (1st November 2016) - Bendixen, Anette Bakkane; Engedal, Knut
Abstract : Objectives: Our aims were to explore prevalence of anxiety among patients admitted to departments of geriatric psychiatry for treatment of various diagnoses and to examine how often anxiety was registered as a previous or ongoing diagnosis. Method: In all, 473 patients admitted to one of five departments of geriatric psychiatry were included in a quality register and examined according to a standardized protocol. The Geriatric Anxiety Inventory (GAI) was used to measure anxiety during the first week after admission. Diagnoses were made at discharge. Results: Using a cutoff on the GAI of 8/9, the prevalence of anxiety for the following diagnostic groups was depression 65.3%, psychosis 28%, dementia 38.8% and mania 33.3%. Of 24 patients with a primary diagnosis of anxiety, 66.7% scored above 8 on the GAI. Of 236 patients with a GAI score above 8, only 22 (9.3%) were reported to have a comorbid anxiety disorder by the treating psychiatrist. In a multiple regression analysis, we found that the severity of depression (beta 0.585, p < 0.001), being female (beta 0.096, p 0.028) and the use of antipsychotic drugs (beta 0.129, p 0.006) and anxiolytic drugs (beta 0.129, p 0.005) were associated with a higher GAI score. Conclusion: Anxiety is common in geriatric psychiatric patients, regardless of the primary diagnosis. Our findings suggest that anxiety is often a hidden comorbidity in various psychiatric disorders. A high score on the GAI was associated with the severity of depression, female gender and the use of antipsychotic and anxiolytic drugs.